High fire frequency in California chaparral reduces postfire shrub regeneration and native plant diversity - Ashley R. Grupenhoff; Hugh D. Safford (Ecosphere)
Abstract Fire is crucial for maintaining species diversity and resilience in fire‐adapted shrublands of the world's Mediterranean climate zones (MCZs), which include the chaparral shrublands of the North American MCZ. Chaparral is adapted to high‐intensity burning, with relatively long intervals between fires (30–100 years) typifying undegraded conditions. Modern fire frequencies are much higher in chaparral, driven largely by high densities of human ignitions and coincidence between ignitions and severe weather conditions. This change in the fire regime has major implications for biodiversity, leading to exotic invasion, decreased ecosystem services, and potential type conversion of shrubland to grassland dominated by exotic species. We studied the impact of increased fire frequencies on the composition and abundance of herbaceous and woody species in the Interior Coast Range of northern California. Our study area is one of the most frequently burned areas in California, which allowed us to investigate higher fire frequencies than previously published in the scientific literature for California. We surveyed fifty‐four 250‐m2 plots to assess changes in plant community composition and postfire regeneration of chaparral shrubs across a wide range of fire frequencies, including plots that have burned up to six times in the past 30 years. Our findings reveal that short‐interval fires significantly reduced postfire native woody regeneration, with obligate seeding species experiencing a 99% reduction and facultative species showing an 83% reduction in regeneration in the most frequently burned plots. Moreover, the overall marginal effect of one additional fire since 1985 decreased the proportion of native species cover by 12% and both richness and Shannon diversity by 4%. Consequently, areas with higher fire recurrence supported a more structurally and botanically homogeneous landscape dominated by a homogeneous group of non‐native species.